The impact of climate change on depression in rural Chinese older adult - Chen Liu; Kaihua Zhang; Chenze Zhao; Yufeng Yan; Jinye Li (Frontiers in Public Health)
IntroductionIn recent years, the impact of climate change on the economy and society has become increasingly significant, with depression emerging as a major factor hindering individuals' daily functioning and quality of life. Rural older adult, due to their low income and inadequate social security, face particularly prominent depressive symptoms. However, existing research has predominantly focused on developed countries, with insufficient attention paid to depressive disorders among rural older adult populations in China.MethodsThis study, based on data from the China Health and Retirement Longitudinal Study (CHARLS) from 2013 to 2020 and meteorological monitoring data, employs a two-way fixed effects model to examine the effects of climate change on depressive symptoms in rural older adult.ResultsThe findings reveal that: (1) extreme low temperatures are the primary climatic factor increasing depression risks of rural older adult; (2) the depression of women, those with low education levels, those engaged in agricultural activities, and widowed individuals is more significantly affected by low temperatures; (3) climate change directly heightens depression risks among rural older adult through heightened social isolation and loneliness. (4) climate change indirectly exacerbates depression risks through deteriorating physical health, reduced outdoor activities, declining cognitive abilities, and decreased sleep quality.DiscussionThis study provides empirical evidence for policymakers to assess the health costs of climate change and propose targeted interventions for depressive disorders.